VALUE OF 24-HOUR BLOOD PRESSURE MONITORING IN THE DIAGNOSIS OF ARTERIAL HYPERTENSION IN PATIENTSWITH GOUT - E I Markelova; V G Barskova; A E Il'ina; E L Nasonov; E I Markelova; V G Barskova; A E Ilyina; E L Nasonov (Научно-практическая ревматология)
Objective: To study the detection rate of arterial hypertension in patients with gout by 24-hour blood pressure monitoring (BPM). Results. The study included 93 gouty patients who were arbitrarily divided into 2 groups: 1) 22 (24%) subjects with normal pressure, as measured by the Korotkov method; 2) 71 (76%) patients with elevated blood pressure (BP). All the patients underwent 24-hour BPM. Various 24-hour BPM abnormalities (increases in average daily BP, pulse pressure, load-induced pressure indices, impaired daily BP profile) were found in 100% of the patients in both groups), which is indicative of the presence of latent arterial hypertension in Group 1 patients with gout. Conclusion. The found 24-hour BPM abnormalities in gouty patients with normal BP, as measured by the Korotkov method, indicate that these patients have latent AH.